2022
DOI: 10.1371/journal.pntd.0010700
|View full text |Cite
|
Sign up to set email alerts
|

Safety of integrated preventive chemotherapy for neglected tropical diseases

Abstract: Background Preventive chemotherapy (PC) is a central strategy for control and elimination of neglected tropical diseases (NTDs). Increased emphasis has been given to “integration” of NTD programs within health systems and coadministration of NTD drugs offers significant programmatic benefits. Guidance from the World Health Organization (WHO) reflects current evidence for safe drug coadministration and highlights measures to prevent choking of young children during PC. Methodology To understand how coadminist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Between 2016 and 2019, more than 1 billion people received PC each year, resulting in significant reductions in morbidity, reduced transmission, and for some NTDs, regional elimination as a public health problem 28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2016 and 2019, more than 1 billion people received PC each year, resulting in significant reductions in morbidity, reduced transmission, and for some NTDs, regional elimination as a public health problem 28…”
Section: Resultsmentioning
confidence: 99%
“…Between 2016 and 2019, more than 1 billion people received PC each year, resulting in significant reductions in Global Health morbidity, reduced transmission, and for some NTDs, regional elimination as a public health problem. 28 Moreover, decrease of disease transmission averts DALYs in many population groups including uninfected people and future generations.…”
Section: Main Categoriesmentioning
confidence: 99%
“…More importantly, the collaborative support provided by the Senegal national malaria and NTD control programmes made the implementation of the integrated strategy logistically feasible. These factors have been documented to be effective strategies in the vertical implementation of MDA and SMC in most African settings [ 25 , 27 , 28 ]. Therefore, replicating the strategies in implementing an integrated approach in malaria-helminth co-endemic countries will optimize SMC and NTD control programmes.…”
Section: Discussionmentioning
confidence: 99%
“…This finding resonated with the feedback obtained through qualitative interviews conducted among the parents/caregivers of the children enrolled in this trial, during which they expressed concerns about the bitter taste, smell, and vomiting-induced effect of praziquantel [ 29 ]. Previous studies have also documented the increased incidence of these adverse events with praziquantel [ 28 , 30 ]. Amodiaquine, which is a partner drug in the SMC regimen, has also been reported to cause nausea and vomiting in children [ 31 ], but this was not a significant issue in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Central or fixed-point MDAs are used for many NTD elimination and control programmes. Previous studies have found that bringing the entire community together saves on both cost and time compared to house-to-house treatment, in particular in communities where houses are far apart and difficult to reach [ 11 , 12 ]. A downside of this approach is that it shifts much of the participation burden on to communities and may create barriers to access.…”
Section: Discussionmentioning
confidence: 99%